2021
DOI: 10.3390/jcm10091905
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intraocular Pressure and Other Biomechanical Parameters to Distinguish between Subclinical Keratoconus and Healthy Corneas

Abstract: (1) Purpose: To assess the main corneal response differences between normal and subclinical keratoconus (SCKC) with a Corvis® ST device. (2) Material and Methods: We selected 183 eyes of normal patients, of a mean age of 33 ± 9 years and 16 eyes of patients with SCKC of a similar mean age. We measured best corrected visual acuity (BCVA) and corneal topography with a Pentacam HD device to select the SCKC group. Biomechanical measurements were performed using the Corvis® ST device. We carried out a non-parametri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Currently, the ORA is the most commonly used clinical device that has been inferred to measure corneal biomechanical properties. 42 The ORA measures hysteresis, which weakly correlates with corneal thickness and is a measure of the difference in the deformation that occurs during loading and unloading of the cornea. 7 Alterations in hysteresis can be observed in some conditions that affect the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the ORA is the most commonly used clinical device that has been inferred to measure corneal biomechanical properties. 42 The ORA measures hysteresis, which weakly correlates with corneal thickness and is a measure of the difference in the deformation that occurs during loading and unloading of the cornea. 7 Alterations in hysteresis can be observed in some conditions that affect the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…The SP variable A1 is the most important determinant variable in classifying and identifying subclinical keratoconus, followed by A2 Time. Peris-Martinez et al [ 33 ] published that A2 speed was the best parameter to diagnose patients with subclinical keratoconus. In a recent study, Ren et al [ 34 ] demonstrated that ARTh and SP-A1 variables were lower in eyes with subclinical keratoconus than in normal eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Peris-Martínez et al [27] published a report that A2 velocity was the best parameter to diagnose SCKC patients. According to our results, A2 velocity presented statistically significant differences between SCKC and healthy corneas.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the SCKC sample size must be increased in future investigations. However, similar SCKC eyes have been evaluated in previously published studies [25,27,[37][38][39] (between 12 and 28 SCKC). The lack of validation in an independent cohort is truly a significant limitation common to all biomedical investigations.…”
Section: Discussionmentioning
confidence: 99%